Expression of Na+/K+-ATPase Was Affected by Salinity Change in Pacific abalone Haliotis discus hannai - Jia, Yanglei; Liu, Xiao (Frontiers in Physiology, 2018)
Na+/K+-ATPase (NKA) belongs to the P-type ATPase family, whose members are located in the cell membrane and are distributed in diverse tissues and cells. The main function of the NKA is to regulate osmotic pressure. To better understand the role of NKA in osmoregulation, we first cloned and characterized the full-length cDNAs of NKA α subunit and β subunit from Pacific abalone Haliotis discus hannai in the current study. The predicted protein sequence of the NKA α subunit, as the catalytic subunit, was well conserved. In contrast, the protein sequence of the β subunit had low similarity with those of other species. Phylogenetic analysis revealed that both the α and β subunits of the NKA protein of Pacific abalone were clustered with those of the Gastropoda. Then, the relationship between salinity changes and the NKA was investigated. Sudden salinity changes (with low-salinity seawater (LSW) or high-salinity seawater (HSW)) led to clear changes in ion concentration (Na+ and K+) in hemolymph; however, the relative stability of ion concentrations in tissue revealed that Pacific abalone has a strong osmotic pressure regulation ability when faced with these salinity changes. Meanwhile, the expression and activity of the NKA was significantly decreased (in LSW group) or increased (in HSW group) during the ion concentration re-establishing stages, which was consistent with the coordinated regulation of ion concentration in hemolymph. Moreover, a positive correlation between cyclic adenosine monophosphate (cAMP) concentrations and NKA mRNA expression (NKA activity) was observed in mantle and gill. Therefore, the sudden salinity changes may affect NKA transcription activation, translation and enzyme activity via a cAMP-mediated pathway.